Beam filtering in industrial X-ray computed tomography - Mutiargo, Bisma (2019)
X-ray CT is considered as the future of non-destructive evaluation and metrology scanning device. The emergence of industry 4.0 sees a rising adoption of additive manufacturing application in the manufacturing industry and hence a higher utilisation demand for X-ray CT. Industrial X-ray CT is a polychromatic source that releases X-ray energy in different energies and it is usually dominated with low energy X-rays. Due to the underlying physical constrain surrounding X-ray physics, a physical filter are often needed to remove the low energy X-rays. A proper filtering will remove image artefacts due to low energy X-ray presence. Despite this, it is known that there is insufficient methodology for a proper X-ray filtering for an X-ray operator to adhere to. An operator typically relies on operating experience to judge on the material type and thickness of the filter. This means that the decision may differ from one operator to another. This different methodologies from one operator to another can lead to different image quality and a non-standardisation of the result. When the X-ray CT is used by the operator for measurement purposes, the steps taken has to be traceable and standardised. In this project, a review of literature landscape on theoretical quantification of image quality based on filtering decision is done and the theories are then compiled in an excel database to be used as an optimisation method. The theoretical simulation were then verified with real experimental data to verify the correlation between the data and theoretical simulation. The result shows a significant correlation between the simulation and multiple experimentation data between different machines. This means that the simulation software developed in this project can be used as a benchmark for a standardised filter choosing methodology which was then implemented as a standard operation procedure in Advanced Remanufacturing and Technology Centre (ARTC).